Toward developing performance metrics for library print-based specialized collections using available circulation data and ratio analysis. Issue 4 (1st October 2020) - Hicks, Sarah; Behary, R.
Abstract: The purpose of this study is to contribute to the establishment of metrics that can be used by libraries to analyze, anticipate, and plan for resource allocation for specialized print-based collections within an academic library. In the context of transactions associated with the circulation of library materials, that is checkouts, renewals, and holds, the resources this study will propose includes two ratios that can be used for evaluating and justifying continued allocation of library resources to specialized print collections. These ratios proposed are the Proportionate Number (P/N) and Internal P/N (I-P/N) Ratios. Beginning with the conceptual framework of how data driven decision making can contribute to the operation of the library, the study will also provide concrete examples of how to analyze data from an Integrated Library System (ILS). Data will be presented for the case study of Gumberg Library at Duquesne University. The study hopes to address a perceived gap in the literature that percentage of users accessing a collection is often not considered in the analysis of circulation data.